If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -6 = 14 + -3n Reorder the terms: -6 + 7n = 14 + -3n Solving -6 + 7n = 14 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. -6 + 7n + 3n = 14 + -3n + 3n Combine like terms: 7n + 3n = 10n -6 + 10n = 14 + -3n + 3n Combine like terms: -3n + 3n = 0 -6 + 10n = 14 + 0 -6 + 10n = 14 Add '6' to each side of the equation. -6 + 6 + 10n = 14 + 6 Combine like terms: -6 + 6 = 0 0 + 10n = 14 + 6 10n = 14 + 6 Combine like terms: 14 + 6 = 20 10n = 20 Divide each side by '10'. n = 2 Simplifying n = 2
| -48-8x=31-15x | | (x+5)-2(3-4x)=4(x+5)-1 | | -4=-6n-(6n-2) | | 8x+-8=x+7 | | 4(x+2)+6x=20 | | 2x-1overx=-1 | | -6/5*30 | | -50y=3y-8 | | 2c^3-4c^2-70c=0 | | 2(x-2)+x+x+3=25 | | 5n-16=8n-10 | | 2*ln(x+1)=ln(2x) | | 2x^2+28x+103=30 | | 15x-20=8x+16+5 | | 2+-3/4=6 | | [s+3(s-1)]=18 | | 5/7/35 | | 10-1/2x=6x-3 | | 18+c/4=32 | | 18+c/4=32 | | -6.8-(-6.4)= | | (X+2)-2(2-2x)=2(x+4)-1 | | 28000n+3000n=36000n+2000n | | -3*(h-6)=5*(2h+3) | | 6(x+5)*4=3x-5 | | 0.5x+0.5=x+1 | | 4+-45= | | 16/4/5 | | 7+6x=4x-13 | | -3x^2-7x+5= | | 40+x=60 | | 15-4z=10 |